PENGARUH FILSAFAT POSITIVISME DALAM PENEGAKAN HUKUM DI INDONESIA - -, Maryanto - (Wacana Hukum, 2013)
Abstract: The principles of legal certainty very dominating in the law enforcement in Indonesia. The principle of legal certainty that comes from century XVII/XVIII in Europe is a great idea from tangible in writing, made by competent authorities. The term of analytical jurisprudence indicates that the law shoul be removed from the study of metaphysics. Doctrine analytical jurisprudence annnot be implemented just after about two centuries introduction by the originators. It is doe to changes and development of society so rapidly. For those in law enforcement must look spirit and the time made law. Don’t just look at the text but the context of the law with the purpose of the law. Key word: law enforcement, Analytical Jurisprudence,religion models of reinforcement.